Associations of Coffee and Tea Consumption With Survival to Age 90 Years Among Older Women. Issue 9 (24th April 2020) - Shadyab, Aladdin H.; Manson, JoAnn E.; Luo, Juhua; Haring, Bernhard; Saquib, Nazmus; Snetselaar, Linda G.; Chen, Jiu‐Chiuan; Groessl, Erik J.; Wassertheil‐Smoller, Sylvia; Sun, Yangbo; Hale, Lauren; LeBoff, Meryl S.; et al.
Abstract : BACKGROUND: Coffee and tea are two of the most widely consumed beverages worldwide and have been associated with reduced risk of mortality in some studies. However, it is unknown whether consumption of these beverages is associated with survival to an advanced age. OBJECTIVE: To examine associations of coffee and tea consumption with survival to age 90 years. DESIGN: Prospective cohort study among participants from the Womenʼs Health Initiative, recruited during 1993 to 1998 and followed up until March 31, 2018. SETTING: The setting included 40 US clinical centers. PARTICIPANTS: A racially and ethnically diverse cohort of 27, 480 older women, aged 65 to 81 years at baseline. MEASUREMENTS: Women were classified as having either survived to age 90 years or died before this age. Consumption of caffeinated and decaffeinated coffee and caffeinated tea was assessed at baseline and categorized as 0, 1, 2 to 3, or 4 or more cups/day. Associations of coffee and tea consumption with survival to age 90 years were examined using logistic regression models adjusted for sociodemographic characteristics, lifestyle behaviors, dietary quality, and chronic disease history. RESULTS: A total of 14, 659 (53.3%) women survived to age 90 years during follow‐up. Caffeinated coffee, decaffeinated coffee, or caffeinated tea consumption was not significantly associated with survival to age 90 years after adjusting for confounders. Findings did not significantly vary by smoking, body mass index, or race/ethnicity. CONCLUSION: No amount of coffee or tea consumption was associated with late‐age survival among older women. These findings may be reassuring to older women who consume coffee and tea as part of their daily diets but do not support drinking these beverages to achieve longevity.